Impact of macro shocks on sovereign default probabilities - Marco Shinobu Matsumura (Institute for Applied Economic Research (ipea), 2015)
We use macro finance models to study the interaction between macro variables and the Brazilian sovereign yield curve using daily data. We calculate the model implied default probabilities and a measure of the impact of macro shocks on the probabilities. An extension of the Dai-Singleton identification strategy for Gaussian models with latent and observable factors is described in order to estimate our models. Among the tested variables, VIX is the most important macro factor affecting short term bonds and default probabilities and the Fed short rate is the most important factor affecting the long term default probabilities.
Keywords: C13; C32; E44; E52; G12; G13; 330